Clinical and Laboratory Parameters of Carp Edema Virus Disease: A Case Report - Papežíková, Ivana; Piačková, Veronika; Dyková, Iva; Baloch, Ali Asghar; Kroupová, Hana Kocour; Zusková, Eliška; Pojezdal, Ľubomír; Minářová, Hana; Syrová, Eva; Banďouchová, Hana; Hyršl, Pavel; Matějíčková, Kateřina; et al. (Viruses, 2023)
In the present study, we describe a natural outbreak of carp edema virus disease (CEVD) in koi carp, concentrating on clinical manifestation, gross and microscopic pathology, immunological parameters, viral diagnostics, and phylogenetic analysis. Examination of white blood cell parameters showed increased monocyte and decreased lymphocyte counts in CEV-affected fish compared to healthy control fish. Regarding immune system functioning, the present work shows, for the first time, enhanced phagocytic activity in CEV-affected fish. Respiratory burst of phagocytes was strongly increased in diseased fish, the increase being attributed to an increased phagocyte count rather than enhancement of their metabolic activity. The present work also newly shows histopathological changes in the pancreatic tissue of diseased koi.
Keywords: histology; Carps; Poxviridae; immunology; infekce vyvolané poxviry; nemoci ryb; Edema; Animals; koi sleepy disease; Poxviridae Infections; edém; Phylogeny; zvířata; fylogeneze; Fish Diseases; kapři; respiratory burst